Analysis of Company Financial Performance Through Financial Ratios in MSMEs in Malang City and West Manggarai Regency - Ludovikus Kalangsa Meke; Cakti Indra Gunawan; Yayuk Sulistyowati (International Journal of Management and Business, 2026)
This study analyzes the financial performance of MSMEs in Malang City (represented by Aurel Caffe MSME) and West Manggarai Regency (represented by Taka Caffe MSME) through financial ratios of liquidity, solvency, profitability, and activity based on the balance sheet and profit and loss statements in 2025. Using a quantitative descriptive approach with primary data from the financial statements of selected MSMEs via purposive sampling (a total of 2 MSME samples from two regions), the analysis was carried out with standard formulas such as quick ratio, debt to equity ratio, ROA, ROE, and inventory turnover. The results show that Aurel Caffe MSME (Malang) has good liquidity (quick ratio 188.99; cash ratio 3.71) but less than optimal solvency and profitability (debt ratio 0.578; ROA 0.915), while Taka Caffe MSME (West Manggarai) excels in profitability (profit margin 1.163; ROE 1.42) but lower liquidity (quick ratio 171.99). Overall, the financial performance of both MSMEs is quite good with significant differences due to location factors, where Malang is stronger in liquidity and West Manggarai in asset activity.